THE INFLUENCE OF WORK EXPERIEMCE, EDUCATION AND TRAINING ON CAREER DEVELOOMENT OF BPS (CENTEAL STATISTICS AGENCY) EMPLOYEES IN SOUTH SULAWESI THOROUGH THE MEDIATING ROLE OF WORK ACHIEVEMENT USING INTERVENING VARIABLE - Yusdayana, Yusdayana; Muspa, Muspa; Hatta, Moh. (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of work experience, education, and training on employee career development, with work performance as an intervening variable, at the Central Statistics Agency (BPS) of South Sulawesi Province. The study used a quantitative approach with survey methods and path analysis to examine the relationships between variables. The results showed that work experience directly had no significant effect on career development, but through work performance, work experience had a positive and significant influence. Education and training had a positive and significant effect on both work performance and career development, demonstrating the importance of improving employee competency. Work performance proved to be a key factor in driving career development, acting as a bridge between experience or education and career advancement. This study confirms that career development at BPS of South Sulawesi Province is more influenced by actual work results than administrative factors such as seniority, so that self-development strategies through education, training, and performance achievement are key to employee career success.